Kemampuan komunikasi matematis siswa pada materi persamaan dan fungsi kuadrat berdasarkan gender di desa sukamenak - Alisa Mutiarani; Deddy Sofyan (Jurnal Inovasi Pembelajaran Matematika: PowerMathEdu, 2022)
Communication plays an important role in assisting students in constructing concepts and establishing links between abstract ideas and language and mathematical symbols. The purpose of this study was to determine students' mathematical communication skills on the material of equations and quadratic functions in terms of gender differences in Sukamenak village. The population in this study were students of SMP/MTs equivalent in the village of Sukamenak, while the sample was selected based on purposive sampling technique, with as many as 6 students consisting of 3 male students and 3 female students. Based on the description and analysis of the results of the research that has been done, it is known that male students get an overall score of 45, with a percentage of 75%, so that they are included in high mathematical communication skills, while female students get an overall score of 50, with a percentage of 83%, so it is included in the category of high mathematical communication skills. So, it can be concluded that the students' mathematical communication skills in the matter of equations and quadratic functions in Sukamenak village in terms of gender differences obtained similarities, both male students and female students belonging to the high category of mathematical communication skills.Komunikasi memainkan peranan yang penting dalam membantu siswa dalam membina konsep dan membina perkaitan antara ide dan bahasa abstrak dengan simbol matematika.Tujuan penelitian ini adalah untuk mengetahui kemampuan komunikasi matematis siswa pada materi persamaan dan fungsi kuadrat ditinjau dari perbedaan gender di desa sukamenak. Populasi dalam penelitian ini adalah siswa SMP/MTs sederajat yang berada di desa sukamenak, sedangkan sampel dipilih berdasarkan teknik purposive sampling sebanyak 6 orang siswa yang terdiri dari 3 orang siswa laki-laki dan 3 orang siswa perempuan. Berdasarkan deskripsi dan analisis hasil penelitian yang telah dilakukan, diketahui bahwa: Siswa laki-laki memperoleh keseluruhan skor sebanyak 45, dengan persentase sebesar 75%, sehingga termasuk dalam kemampuan komunikasi matematis yang tinggi, sedangkan siswa perempuan memperoleh keseluruhan skor sebanyak 50, dengan persentase sebesar 83%, sehingga termasuk dalam kategori kemampuan komunikasi matematis yang tinggi. Jadi, dapat disimpulkan bahwa kemampuan komunikasi matematis siswa pada materi persamaan dan fungsi kuadrat di desa Sukamenak ditinjau d perbedaan gender diperoleh kesamaan, baik siswa laki-laki maupun siswa perempuan tergolong kedalam kemampuan komunikasi matematis kategori tinggi.